Silicon-carbon composite material and anode comprising same

Existing electrochemical energy storage solutions are solved by using silicon-carbon composites of porous carbon scaffolds, silicon, nanoparticles, and nanowires in the anode of electrochemical energy storage devices, and coating their surfaces with surface coatings of specific elements. Where the device falls short in charging performance and cycle stability, it achieves faster charging times and greater cycle stability and long life.

CN119365990APending Publication Date: 2025-01-24SELFOSS GRP GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380046529.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing electrochemical energy storage devices have shortcomings in charging performance and cycle stability, especially in terms of efficient charging and long life.

Method used

Silicon-carbon composite materials containing porous carbon brackets, silicon, nanoparticles, and nano-norms are used as the anode material and coated with specific elements on its surface to improve electrochemical performance.

Benefits of technology

It has significantly improved the charging characteristics of electrochemical energy storage devices, including faster charging time and higher cycle stability and long life, and improved the overall performance of electrochemical energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365990A_ABST
    Figure CN119365990A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite (10) comprising:-a porous carbon scaffold comprising micropores and mesopores and having a total pore volume greater than 0.5 cm3 / g; -a silicon content in the range of > = 30 wt.-% to < = 75 wt.-% relative to the silicon-carbon composite material (10); -nanoparticles comprising at least one of the elements Cu, Fe or Ni, where the nanoparticles are positioned on the surface of the silicon-containing carbon scaffold; and-a nanowire selected from the group consisting of silicon nanowires and carbon nanowires; wherein the nanowires are grown on the nanoparticles, and wherein a first surface coating is provided which is applied at least partially on a first surface region of the silicon-carbon composite material (10), the surface coating comprising at least one element selected from the group consisting of C, Al, Si, Ti, Zr and Nb. The invention further relates to an anode (110) comprising such a silicon-carbon composite material (10).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a silicon-carbon composite material which exhibits improved properties, in particular when used in an anode of an electrochemical energy storage device. The present invention further relates to an anode for an electrochemical energy storage device and to an electrochemical energy storage device comprising such an anode. Background Art

[0002] Electrochemical energy storage devices are well known in the art. In particular, in view of the progress in the electrification of vehicles, electrochemical energy storage devices are becoming increasingly important. For this, in particular in order to gain better acceptance on the market, the charging performance becomes more important.

[0003] In addition, silicon-carbon mixtures are known, which can be produced from carbon materials, which include pore volume, including micropores, mesopores, and / or macropores. Such carbon mixtures can be used as a support for producing silicon-carbon composite materials. The pore volume of porous carbon materials impregnated with silicon can be achieved with silicon provided in nanometer size. Generally, silicon has a significantly higher energy density than, for example, graphite. For example, the energy density of silicon is ten times that of graphite.

[0004] After impregnation, such impregnated carbon materials can be coated in order to further reduce the porous surface still present. Possible coatings can consist, for example, of polymers, in particular conductive polymers, carbon or metal oxides.

[0005] In addition, the carbon material impregnated with silicon can be used in combination with other materials as a material composition. Known material compositions contain binders and / or carbon particles. Such material compositions are typically used as electrode materials, especially anode materials, in electrochemical cells, especially lithium-ion battery cells.

[0006] For example, U.S. Publication No. 2017 / 0170477 discloses a composite material comprising a porous carbon support and silicon, wherein the composite material comprises 15 to 85 wt % silicon and has a thickness of 0.05 cm 3 / g to 0.5cm 3 / g range, and wherein the composite material comprises a nitrogen inaccessible volume within 1.5 g / cm 3 Up to 2.2g / cm 3 A plurality of particles within a range of particle scaffold densities.

[0007] Due to the rapidly increasing importance of electrochemical energy storage devices, in particular Li-ion batteries, there is a constant need for further developments and improvements in the field of forming such devices. Summary of the invention

[0008] Based on the above, an object of the present invention is to at least partially overcome at least one disadvantage of the prior art. In particular, an object of the present invention is to provide measures for providing improved charging characteristics in electrochemical energy storage devices. Another object of the present invention is to provide measures in electrochemical energy storage devices that show good cycle stability and long life.

[0009] These objects are at least partially solved by a silicon-carbon composite material according to claim 1 .

[0010] A method for preparing a surface-coated silicon-carbon composite material according to claim 1, an anode according to claim 14, a method for manufacturing an anode according to claim 15, an electrochemical storage device according to claim 19, and an electric vehicle according to claim 20. Preferred embodiments of the invention are described in the dependent claims and the following description, each of which may represent an aspect of the invention alone or in combination unless expressly excluded. When a feature is shown in combination with another feature, this is only to simplify the description of the invention and is by no means intended to imply that the feature cannot be another feature of the invention without the other feature.

[0011] A silicon-carbon composite material is described comprising:

[0012] - A porous carbon scaffold comprising micropores and mesopores with a total pore volume greater than 0.5 cm 3 / g;

[0013] - a silicon content (silicon content) in the range of ≥30 wt.-% to ≤75 wt.-%, relative to the silicon-carbon composite material;

[0014] - nanoparticles comprising at least one of the elements Cu, Fe or Ni, wherein the nanoparticles are positioned on the surface of the silicon-containing carbon support, and

[0015] - nanowires selected from silicon nanowires and carbon nanowires; wherein the nanowires are grown on nanoparticles, and wherein a first surface coating is provided, the first surface coating being at least partially applied on a first surface region of the silicon-carbon composite material, the surface coating comprising at least one of the elements selected from C, Al, Si, Ti, Zr and Nb.

[0016] Such silicon-carbon composite materials are not known in the prior art, but show significant advantages over prior art solutions, in particular when used in anodes of electrochemical energy storage devices.

[0017] The composite material described is a silicon-carbon composite material and therefore contains at least the elements silicon and carbon, wherein the silicon is provided in the pores of the carbon support.

[0018] The term carbon refers to a material or substance consisting of or at least comprising carbon. To this end, carbon materials can include high purity, amorphous and crystalline materials. Carbon can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel or a combination thereof. In a further embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. To this end, polymers are molecules comprising two or more repeating structural units. Porous carbon provides advantages of being generally easy to produce, generally having low impurities and large pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio as described in more detail below.

[0019] In a further embodiment, the carbon is a hard carbon material, graphite carbon, or an oxide containing compound. For example, the oxide containing compound is silicon oxide (SiO2). Alternatively, the oxide containing compound is titanium oxide (TiO2), tin oxide (SnO2), or other oxides. The hard carbon material is a non-graphitizable carbon material. Hard carbon provides the advantage that it remains amorphous at elevated temperatures (typically >1500°C), while "soft" carbon crystallizes and becomes graphite.

[0020] In one embodiment, the carbon can be a modified hard carbon. The modified hard carbon is a composite material comprising both carbon (particularly hard carbon) and a lithium alloy material. The lithium alloy material can be silicon, tin, germanium, nickel, aluminum, manganese, aluminum oxide (A12O3), titanium, titanium oxide, sulfur, molybdenum, arsenic, gallium, phosphorus, selenium, antimony, bismuth, tellurium or indium or any other metal or metalloid capable of absorbing lithium.

[0021] The silicon portion may be pure silicon or a material composition containing silicon. For example, the silicon portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), a silicon-nickel alloy (Si-Ni). In further embodiments, the silicon portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.

[0022] The presence of silicon in the silicon-carbon composite material and in particular in its pores can be advantageous because, in general, silicon has a significantly higher energy density than, for example, graphite. For example, the energy density of silicon exceeds energy density of graphite by a factor of ten.

[0023] The silicon-carbon composite material comprises a porous carbon scaffold including micropores and mesopores and having a total pore volume greater than 0.5 cm 3 / g. Typically, porous carbon has pore space, also referred to as pore volume, wherein the pore space is a group of voids (pores) in the carbon that can be filled with a gas or fluid. This embodiment can significantly reduce the weight of the anode, and thus significantly reduce the weight of the electrochemical energy storage device.

[0024] This embodiment can be of the utmost importance, in particular when silicon-carbon composites are used for anodes and correspondingly equipped electrochemical energy storage devices are used in mobile applications, such as in vehicles. In addition, the electrochemical properties can also be improved. For this purpose, porous arrangements offer the advantages of being generally easy to produce, generally having low impurities and a large pore volume. As a result, porous carbons exhibit good electrical conductivity and high mechanical and chemical stability.

[0025] The porous carbon scaffold thus comprises micropores and mesopores. For the purposes of the present invention, micropores are defined as pores with a diameter less than 2 nm, whereas for the purposes of the present invention, mesopores are defined as pores with a diameter between 2 nm and 50 nm.

[0026] Furthermore, the silicon-carbon composite material has a silicon content in an amount of ≥30 wt.-% to ≤75 wt.-%, relative to the silicon-carbon composite material. The silicon content of the total mass of the silicon-carbon composite material is typically between 30% and 75%, in particular between 40% and 60%. This embodiment can improve the charging process in a very effective way, in particular with regard to charging time or other charging characteristics.

[0027] The silicon-carbon composite material further comprises nanoparticles. The nanoparticles comprised are characterized in that they comprise at least one of the elements Cu, Fe and Ni. For the purposes of the present invention, comprising the elements Cu, Fe and Ni shall mean that the nanoparticles comprise the elements in pure metal form or as atomic components in a compound or alloy or as metal oxides. It may be particularly preferred that the nanoparticles comprise CuO or Fe2O3. Furthermore and with regard to size, for the purposes of the present invention, nanoparticles are defined as having a maximum diameter in the nanometer range, i.e. in the range of ≤10 nm, such as ≤7 nm. Specifically, the nanowires may have a length in the range of ≥3 nm to ≤10 nm.

[0028] With regard to a specific arrangement, as described below, the silicon-carbon composite material is arranged such that the nanowires are positioned on the surface of the porous and silicon-containing carbon scaffold and can act as seed particles to form the nanowires.

[0029] Therefore, the silicon-carbon composite material further comprises nanowires selected from silicon nanowires and carbon nanowires. Therefore, the silicon-carbon composite material may comprise silicon nanowires, carbon nanowires or a mixture of silicon nanowires and carbon nanowires.

[0030] As a general definition and as generally known in the art, a nanowire is a nanostructure in the form of a wire with a nanometer-scale diameter. More precisely, a nanowire can be defined as a structure with a thickness or diameter defined to tens of nanometers or less, in particular ≤100 nm, such as ≤50 nm, and an indefinite length.

[0031] As is generally known in the art, silicon nanowires (also referred to as SiNWs) are a type of semiconductor nanowire formed by etching a solid or by catalytic growth from a gas or liquid phase, most typically from a silicon precursor. According to the present invention, the nanowires are grown on nanoparticles, which can therefore act as seed particles.

[0032] Preferably, silicon nanowires are provided, the silicon nanowires comprising monocrystalline silicon, polycrystalline silicon or a combination thereof. In other words, it may be preferred if the silicon nanowires comprise only monocrystalline form, only polycrystalline form or a mixture of the latter.

[0033] Corresponding to silicon nanowires, carbon nanowires can be formed, for example, from carbon precursors by etching the solid or by catalytic growth from the gas or liquid phase or in particular by catalytic growth by chemical vapor deposition. Likewise, nanoparticles can be used as seed particles.

[0034] In addition, a first surface coating is provided, which is at least partially applied on a first surface region of the silicon-carbon composite material comprising at least one of the elements selected from C, Al, Si, Ti, Zr and Nb. The surface coating and the corresponding region are referred to as the first surface coating and the first surface region, because optionally, a second surface coating and a second surface region may be present, which will be described in more detail below.

[0035] Thus, the first surface coating covers at least a portion of the silicon-carbon composite material, and more specifically, at least partially covers the silicon-containing carbon support together with the nanoparticles and nanowires. The first surface coating comprises at least one of the elements selected from C, Al, Si, Ti, Zr and Nb, and thus comprises only one of these elements or a mixture of two or more of the aforementioned elements. For the purposes of the present invention, comprising the elements Al, Si, Ti, Zr and Nb shall mean that the first surface coating comprises the elements in pure metallic form or as atomic components in a compound or alloy. It is particularly preferred that the first surface coating comprises oxides of the above elements, wherein aluminum oxide (Al2O3) is particularly preferred.

[0036] With regard to the electronic properties of a correspondingly equipped anode, it is particularly preferred that the at least partially applied first surface coating is formed as a layer, wherein the layer of the surface coating has a thickness of >0 nm to ≤0.3 nm and contains amorphous carbon or a metal oxide from at least one or more of the elements Al, Si, Ti, Zr and Nb or a combination of the aforementioned elements.

[0037] It is further preferred that the first surface coating covers at least 50% of the surface area of ​​the silicon-carbon composite material, and thus covers at least 50% of the surface area of ​​the silicon-containing carbon support and nanowires and nanoparticles. For example, the first surface coating covers at least 70% of the surface area of ​​the silicon-carbon composite material, preferably at least 95% of the surface area of ​​the silicon-carbon composite material. As an example, the first surface coating covers 100% of the surface area of ​​the silicon-carbon composite material.

[0038] A benefit of the impregnated and / or coated carbon material is improved stability of the lithium ion storage capacity, which increases the charge capacity of the lithium ion battery cell.

[0039] Such a silicon-carbon composite material achieves the following advantages, according to which excellent electronic properties are achieved. Such properties can in particular allow an improved charging behavior of an anode equipped with the silicon-carbon composite material.

[0040] It may be further preferred that, in addition to the first surface coating that at least partially covers the first surface area of ​​the silicon-carbon composite material, a second silicon-carbon composite material coating is provided. This second surface coating at least partially covers the surface area of ​​the silicon-carbon composite material. Therefore, the surface area of ​​the silicon-carbon composite material is at least partially covered by the first surface coating, and is further covered by the second surface coating. The second surface coating can cover the second surface area of ​​the silicon-carbon composite material, and therefore covers the second surface area of ​​the silicon-containing carbon support, nanoparticles and nanowires. The second surface area may be different from the first surface area, it may partially overlap with the first surface area, or it may be the same as the first surface area. Therefore, the second surface coating is at least partially applied to the top (top, top) of the first surface coating and / or beside and therefore next to the first surface coating.

[0041] Regarding the second surface coating, it may be preferred that the second surface coating is formed as a carbon coating. To this end, the carbon coating may be a pure carbon coating or it may be a coating containing carbon as an element in the coating substance.

[0042] The second surface coating allows a particularly effective implementation of the electrical properties of the material and therefore of the anode equipped with this material.

[0043] Regarding other advantages and technical features of the silicon-carbon composite material, it relates to anodes, methods, and to electrochemical energy storage devices and to vehicles.

[0044] Also disclosed is a method for preparing the surface-coated silicon-carbon composite material as described above, wherein the method comprises the following steps:

[0045] -Providing porous carbon scaffolds with micropores and mesopores;

[0046] - introducing into the micropores and mesopores of the porous carbon support a compound comprising silicon and optionally also at least one of the elements Fe, Al, Ni, W and Ti, in particular by chemical vapor infiltration, to form a silicon-carbon composite material,

[0047] - attaching nanowires chosen from carbon nanowires and silicon nanowires to the porous carbon support, in particular by chemical vapor deposition, wherein the nanowires grow on nanoparticles positioned on the surface of the carbon support, wherein the nanoparticles comprise at least one element chosen from Cu, Fe and / or Ni;

[0048] - applying at least a first surface coating on the surface area of ​​the silicon-carbon composite material, the first surface coating comprising at least one of the elements selected from C, Al, Si, Ti, Zr and Nb, and wherein the first surface coating at least partially covers the surface area of ​​the silicon-carbon composite material.

[0049] This method is suitable for preparing the silicon-carbon composite material as described above.

[0050] The method comprises at least the following steps.

[0051] A porous carbon scaffold having micropores and mesopores is provided. With regard to the definition of micropores and mesopores and further embodiments of the carbon scaffold, reference is made to the above description of the silicon-carbon composite material.

[0052] After providing the porous carbon support, a compound comprising silicon and optionally at least one of the elements Fe, Al, Ni, W and Ti is introduced into the micropores and mesopores of the porous carbon support. With regard to the corresponding compound introduced into the pores, reference is made to the above description of the silicon-carbon composite material.

[0053] Preferably, the compounds are introduced into the micropores and mesopores of the porous carbon support by chemical vapor infiltration (also called CVI). Such a procedure is known per se and offers significant advantages in the present application. For example, the infiltration can be achieved in a very defined manner also in very small pores (i.e. in micropores and mesopores). Therefore, the infiltrated product and therefore the silicon-carbon composite material also have defined properties, which in turn allows the production of electrodes in a very reproducible manner.

[0054] The method further comprises a step according to which nanowires selected from carbon nanowires and silicon nanowires are attached to the porous carbon support. This can be achieved, for example, by chemical vapor deposition as described above.

[0055] Specifically, the nanowires are grown on nanoparticles positioned on the surface of the carbon support, wherein the nanoparticles include at least one element selected from Cu, Fe and / or Ni. For the purposes of the present invention, including the elements Cu, Fe and Ni shall mean that the nanoparticles include the elements in pure metallic form or as atomic constituents in compounds such as alloys or oxides. Therefore, prior to growing the nanowires, nanoparticles acting as seed particles are positioned on the surface of the silicon-containing carbon support.

[0056] About nanoparticles. Reference is made to the above description. The nanoparticles included are characterized in that they include at least one of the elements Cu, Fe and Ni. For the purposes of the present invention, including the elements Cu, Fe and Ni shall mean that the nanoparticles include the elements in pure metallic form or as atomic constituents in compounds such as alloys or oxides. Particularly preferably, the nanoparticles include CuO or Fe2O3.

[0057] Preferably, the nanowires, i.e. silicon nanowires and / or carbon nanowires, are attached to the porous carbon support by nanoparticles such as CuO or Fe2O3. Silicon nanowires and carbon nanowires can be synthesized by using chemical vapor deposition methods (e.g. by using SiH4 or C2H2) and the catalytic behavior of copper oxide growing such Si and C nanowires on nanoparticles. This method allows very reproducible results, so that the resulting structures in turn show very reproducible properties.

[0058] After attaching the nanowires to the carbon support, a further step is provided, which includes applying at least a first surface coating on the surface region of the silicon-carbon composite material to form a surface-coated silicon-carbon composite material, the coating at least partially covering the surface region of the silicon-carbon composite material.

[0059] With regard to the applied surface coating, the surface coating comprises at least one of the elements selected from C, Al, Si, Ti, Zr and Nb. Generally, it is preferred that the first surface coating comprises a metal oxide from at least one of the elements Al, Si, Zr and Nb. It is particularly preferred that the first surface coating comprises aluminum oxide or zirconium oxide or carbon.

[0060] It may cover at least 50% of the surface of the silicon-carbon composite material. In an exemplary embodiment, the first surface coating may cover all surface areas of the silicon-carbon composite material.

[0061] Preferably, at least one surface coating of the surface region of the silicon-carbon composite material with silicon and / or carbon nanowires is applied by a vapor deposition method.

[0062] It is further preferred that the silicon-carbon composite material is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound surface. The compound surface thus produced is then treated with at least one of moisture or oxygen or ozone to form at least one first surface coating. This embodiment shows a reliable way to provide a surface coating with defined and predictable properties.

[0063] With regard to the aforementioned treatment, it is particularly preferred that the treatment of the silicon-carbon composite material with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound surface and the subsequent treatment of the treated compound surface with moisture or oxygen or ozone are repeated at least once. This embodiment allows a particularly safe and reliable treatment of the treated compound surface, which in turn achieves well-defined surface properties.

[0064] Regarding the treatment of the treated compound with moisture or oxygen or ozone, preferably a temperature in the range of 150°C to 550°C is used.

[0065] In a specific embodiment and for the purpose of explanation, a silicon-containing carbon scaffold together with nanoparticles (such as CuO) and nanowires forms a material which reacts with another reaction medium, such as trimethylaluminum (TMA) (as an example of an alkyl metal compound). This can be achieved in the sense of a so-called atomic layer deposition (ALD) method. Thus, TMA covers the accessible surface and decomposes into Al2O3 in the presence of H2O and in particular at temperatures >250°C.

[0066] Regarding other advantages and technical features of the aforementioned method, it relates to silicon-carbon composite materials, anodes, other methods, and to electrochemical energy storage devices and to vehicles.

[0067] Further described is an anode for an electrochemical energy storage device comprising a silicon-carbon composite as described above.The silicon-carbon composite may be formed with any of the optional features as described above.

[0068] Thus, the anode comprises a silicon-carbon composite material comprising:

[0069] - A porous carbon scaffold comprising micropores and mesopores with a total pore volume greater than 0.5 cm 3 / g;

[0070] - a silicon content in the range of ≥30 wt.-% to ≤75 wt.-% relative to the silicon-carbon composite;

[0071] - nanoparticles comprising at least one of the elements Cu, Fe or Ni, wherein the nanoparticles are positioned on the surface of the silicon-containing carbon support, and

[0072] - nanowires selected from silicon nanowires and carbon nanowires; wherein the nanowires are grown on nanoparticles, and wherein a first surface coating is provided, the first surface coating being at least partially applied on a first surface region of the silicon-carbon composite material, the surface coating comprising at least one of the elements selected from C, Al, Si, Ti, Zr and Nb.

[0073] In general, the anode may comprise a silicon-carbon composite material in an amount of ≥45 wt.-% to ≤90 wt.-% relative to the anode. In general, in this sense, the anode may comprise all materials, preferably present in a binder, attached to an electrical conductor (such as a metal foil). In other words, the amounts provided relate to the anode and therefore the materials present on the conductor.

[0074] In addition to the silicon-carbon composite material, the anode may also include a further silicon-carbon composite material that is different from the first and aforementioned silicon-carbon composite material.

[0075] The anode may further comprise graphite. Graphite is generally known as an anode material for lithium batteries or lithium ion batteries, respectively. Generally, graphite is an excellent anode material and has long been known for lithium ion batteries, which benefits from its relatively low cost, abundance, high energy density, power density, and an incomparable balance of very long cycle life. However, in electrochemical energy storage devices of the prior art, graphite is mainly present as a dominant material in terms of the amount in the composition. Compared to this arrangement and according to the present invention, graphite is present in the anode in a relatively small amount, i.e., in an amount of ≥5wt.-% to ≤47wt.-% relative to the anode.

[0076] Surprisingly it has been found that exchanging the bulk of graphite by means of a carbon-silicon composite material allows even improved properties compared to pure graphite or bulk graphite.

[0077] In addition, a binder is present in the anode. A binder is a binding agent or binding material in a manner known per se. Thus, a binder refers to a material that can hold together the individual components of a substance, in particular particles such as carbon and silicon-carbon composites. The binder is generally arranged so that when the particles are combined with the corresponding binder, a cohesive mass is formed, which can be further shaped into a new form.

[0078] The binder can be configured to bind all compounds present in the anode, such as, in particular, the particularly porous carbon and silicon content (silicon content), graphite and nanowires of the first silicon-carbon composite material. In another embodiment, the binder is adapted to bind additional materials to at least one of the corresponding silicon-carbon composite materials. Thus, the binder is typically arranged to hold together the components of the silicon-carbon composite mixture and the optional additional carbon material that can form an electrode as the anode.

[0079] The anode may contain at least one further binder. This leads to the following advantages: the carbon increases the conductivity of the electrode and thus provides improved conductivity. The at least one further binder also supports mechanical stability.

[0080] The anode may include at least two binders, wherein a first binder is arranged to bind a particularly porous carbon and silicon-carbon portion of a first silicon-carbon composite material and a particularly porous carbon and silicon portion of at least one additional silicon-carbon composite material, and wherein at least one additional binder is arranged to bind the first silicon-carbon composite material to at least one additional silicon-carbon composite material.

[0081] Optionally, the silicon-carbon composite material comprises at least one further binder adapted to bind the first material component and the at least one further material component together.

[0082] For example, the binder is a styrene-butadiene rubber / carboxymethyl cellulose (SBR / CMC) mixture, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA). In an alternative embodiment, the binder is formed as a fluoropolymer, such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), (polyvinylidene fluoride (PCDF), (polytrifluorochloroethylene (PCTFE), trifluoroethanol or a combination of at least one of these materials and at least one other material. In a further embodiment, the binder is a copolymer of polyimide or polyacrylic acid and styrene-butadiene. However, it is particularly preferred that the binder is a styrene-butadiene rubber / carboxymethyl cellulose (CMC / SBR) mixture, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA).

[0083] Generally, the binder may be used in an organic or water-based solution or as a solid binder.

[0084] All the previously described materials, such as in particular silicon-carbon composites, graphite, nanowires connected to nanoparticles, including corresponding coatings, can be provided in a binder on a metal conductor, such as a metal foil, in order to form the final anode.

[0085] The anodes described show the advantage of excellent charging time, which allows the electrochemical energy storage device to be charged from a very low state of charge to a very high state of charge in a very short time. This significantly improves market acceptance. In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles. Therefore, in particular, improving charging time is an important characteristic of secondary batteries for vehicles (such as cars). However, it should be noted that the anodes described herein and therefore the electrochemical energy storage devices are not limited to use in vehicles.

[0086] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.

[0087] The silicon-carbon composite material mixture can be formed so that the silicon-carbon composite material mixture has a range from 0.09 g / cm 3 Up to 1.5g / cm 3 , or from 1.1g / cm 3 and 1.3 g / cm 3 This offers the advantage that the particles are in better contact with one another and thus the conductivity of the resulting electrode is improved.

[0088] In particular, the silicon-carbon composite material mixture has high electrical conductivity. This provides the following advantages: the resistance of the electrode is reduced, thereby allowing Li ions to react with the silicon-carbon composite material mixture more quickly. Therefore, the charging speed of the lithium ion battery can be increased.

[0089] Regarding other advantages and technical features of the aforementioned anode, it relates to silicon-carbon composite materials, methods, and to electrochemical energy storage devices and to vehicles.

[0090] A method of manufacturing an anode as described above is also described, wherein the method comprises the following steps:

[0091] - mixing the silicon-carbon composite material as described above with at least one carbon,

[0092] - combining the mixture of the silicon-carbon composite material and at least one carbon with at least one binder to form an electrode slurry,

[0093] - applying the electrode slurry at least partially onto at least one surface of an electrical conductor, such as a conductor foil, and

[0094] - Drying the conductor foil with applied electrode slurry, in particular at a temperature of ≥ 100° C. to ≤ 140° C., for forming an anode.

[0095] Thus, the method describes a process in which an electrode paste is first formed and then applied to an electrical conductor, such as a metal foil.

[0096] To form the anode, a silicon-carbon composite material having a silicon-containing carbon scaffold decorated with nanowires selected from silicon nanowires and carbon nanowires is mixed with additional carbon, and therefore with pure carbon or a compound containing atomic carbon. The additional carbon is specifically conductive carbon and may be present in order to enhance the conductivity of the anode formed. Graphite may be an example of carbon. Particularly preferably, a homogeneous mixture is formed. This step can generally be achieved by combining the corresponding components and by mixing them in a conventional mixing device. With regard to the silicon-carbon composite material and the nanowires, reference is made to the above description.

[0097] The resulting mixture is then combined with at least one binder to form an electrode slurry. The binder can generally be selected as known in the art and can be similar to the above. The binder can exist as an aqueous solution (i.e., containing water) and / or as a non-aqueous binder solution (i.e., particularly containing an organic solvent). Alternatively, a solid binder can be used. Therefore, this step is used to form an electrode slurry. In the case of using a solid binder, the electrode slurry can be a solid, or in the case of using a binder solution, the electrode slurry can be a pasty substance.

[0098] The electrode slurry is then at least partially applied to at least one surface of an electrical conductor, such as a conductor foil. For the anode, in particular a copper foil can be used. This step can be achieved by a doctor blade method, for example in the case of using a binder solution, or by a calendaring method, for example in the case of using a solid binder.

[0099] Particularly where a binder solution is used but not limited thereto, the applied electrode slurry may be dried to complete the manufacturing process. Typically, drying may be achieved at a temperature in the range of ≥100°C to ≤140°C.

[0100] Regarding other advantages and technical features of the aforementioned method, it relates to silicon-carbon composite materials, anodes, other methods, and to electrochemical energy storage devices and to vehicles.

[0101] Further described is an electrochemical energy storage device comprising:

[0102] - at least one anode as described above;

[0103] - at least one cathode;

[0104] - a separator disposed between the cathode and the anode; and

[0105] - An electrolyte comprising lithium ions.

[0106] The general arrangement of the electrochemical energy storage device can be selected as generally known in the art. In particular, the electrochemical energy storage device can be formed as a lithium-ion battery. However, an important feature of such a device is that it comprises an anode as described in more detail above.

[0107] In addition to the anode, the electrochemical energy storage device or the electrochemical cell of the electrochemical energy storage device comprises a cathode. The cathode can generally be formed as known in the art of lithium batteries.

[0108] In general, the cathode may include a transition metal oxide. In more detail, the cathode may include a 1+ x TM 1-xA single crystal (SC), polycrystalline (PC) or a mixture of single crystal (SC) and polycrystalline (PC) forms of a layered transition metal oxide material of O2, wherein TM is Ni, Co, Mn, Al, Zr, Ti, Nb, W. The amounts of these metals are preferably as follows: Ni = 0.7 to 0.95, Co = 0.01 to 0.15, Mn = 0.01 to 0.1, Al = 0 to 0.03, Zr = 0 to 0.01, Nb, Ti, W = 0 to 0.02, wherein x can be any value between 0 and 0.05. In addition, in the case where there is a mixture of single crystal (SC) and polycrystalline (PC) forms, the mixture ratio can be 20 to 35 wt% SC and 65 to 80% PC.

[0109] In particular, the cathode comprises lithium nickel manganese cobalt oxide, wherein the lithium nickel manganese cobalt oxide is present as a mixture of polymorphs and single crystals. According to this embodiment, the electrochemical properties of the electrochemical energy storage device can be improved even further, in particular with regard to the cycling behavior and in particular with regard to the charging time.

[0110] Regarding the separator, the separator can also be generally formed as known in the prior art. Preferably, the separator can include three layers of polymer. Such a polymer can, for example, include an inorganic coating, such as Al2O3, BaTiO3.

[0111] It may further be preferred that the separator is laminated to the anode. This allows for an improved stacking of electrodes, since the separator is already fixed to the anode electrode.

[0112] The electrolyte may include at least one compound selected from the group consisting of fluoroethylene carbonate, propylene carbonate, ethylene carbonate, lithium hexafluorophosphate, and lithium bis(fluorosulfonyl)imide. It can be shown that when used in a lithium battery, such electrolytes exhibit excellent properties. Typically, the electrolyte may include a mixture of LiPF6 and LiFSi, wherein the electrolyte may be based on fluoroethylene carbonate (FEC)-based substances. It may exemplarily include, each relative to the electrolyte, 1 to 10 wt.-% of FEC, 0 to 20 wt.-% of ethylene carbonate (EC), 0 to 30 wt.-% of propylene carbonate (PC), and optional additional additives.

[0113] The electrochemical energy storage device as described above including the anode exhibits the advantage of excellent charging time, which allows the electrochemical energy storage device to be charged from a very low state of charge to a very high state of charge in a very short time, which significantly improves market acceptance.

[0114] In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles.

[0115] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.

[0116] Regarding other advantages and technical features of the aforementioned electrochemical energy storage device, it relates to silicon-carbon composite materials, anodes, methods, and vehicles.

[0117] An electric vehicle is further described, comprising an electric engine and an electrochemical energy storage device for supplying electrical energy to the electric engine, characterized in that the electrochemical energy storage device is formed as described above.

[0118] The vehicle may generally be any vehicle that is electrically driven. In particular, the electric vehicle may be a fully electric vehicle or a so-called hybrid vehicle. However, it may be preferred that the electric vehicle is a fully electric land vehicle, such as a car, bus or truck.

[0119] The vehicle includes an electric motor and an electrochemical energy storage device for supplying electrical energy to the electric motor.

[0120] The electric motor can generally be arranged as known in the art, for example, the electric drive motor can be a permanent synchronous machine as an electric motor or an asynchronous machine as an electric motor. Of course, both motors can be present and can be supplied with electrical energy from an electrochemical energy storage device. The latter is designed as defined above.

[0121] The anodes and therefore the corresponding electrochemical energy storage devices exhibit the advantage of excellent charging times, which allow the electrochemical energy storage device to be charged from a very low state of charge to a very high state of charge in a very short time. This significantly improves market acceptance.

[0122] In particular, considering secondary batteries used in vehicles, charging time is an important factor that can improve the acceptance of electric vehicles. Therefore, improving charging time in particular is an important characteristic of secondary batteries for vehicles. However, it should of course be noted that the anodes described herein and therefore the electrochemical energy storage devices are not limited to use in vehicles.

[0123] In addition to the above and the charging time, other characteristics of the anode are not deteriorated, such as long life, high cycle stability and damage resistance.

[0124] Regarding other advantages and technical features of the aforementioned vehicle, it relates to silicon-carbon composite materials, anodes, methods, and to electrochemical energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0125] In the following, the invention is explained by way of example with reference to the accompanying drawings and by the accompanying examples of preferred embodiments, wherein the features shown below may each constitute aspects of the invention individually or in combination:

[0126] Figure 1 An exemplary electrochemical storage device having a fabricated anode comprising a silicon-carbon composite material is shown; and

[0127] Figure 2 An exemplary electrochemical storage device according to another embodiment having an anode including a silicon-carbon composite material is shown. DETAILED DESCRIPTION

[0128] In the drawings, the same reference numerals indicate similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some of these elements are enlarged and positioned to improve the legibility of the drawings. Further, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, and are selected only for ease of identification in the drawings.

[0129] Figure 1 A cross-sectional view of an exemplary electrochemical storage device 100 having an anode 110 (also referred to as an anode electrode) including the silicon-carbon composite material 10 is shown.

[0130] The electrochemical storage device 100 is formed as a lithium-ion battery cell. The electrochemical storage device 100 includes at least one anode 110, at least one cathode 120, and a separator 130 disposed between the cathode 120 and the anode 110. The cathode 120 preferably includes a transition metal oxide.

[0131] In addition, an electrolyte 140 containing lithium ions is provided in a cell housing 150 of the electrochemical storage device 100. The electrochemical storage device 100 may be formed as a lithium ion battery cell in a bag form. Therefore, the cell housing 150 may be formed as an aluminum bag. The anode 110, the cathode 120, and the separator 130 are also arranged in the cell housing 150.

[0132] It should be noted that Figure 1 A simplified cross-sectional view is shown. The anode 110, cathode 120 and separator 130 are typically formed as multiple layers that are wound or folded in order to optimize packaging and to increase the possible surface area of ​​the electrolyte 140. In the example shown, only one layer of the components is visible for illustration purposes.

[0133] The anode 110 is coated on both sides with the silicon-carbon composite material 10. The surface coating 11 of the silicon-carbon composite material 10 is achieved on the surface area of ​​the silicon-carbon composite material 10 that is not in contact with the current collector 111 of the anode 110.

[0134] By utilizing an anode 110 having a silicon-carbon material 10, electrical performance is significantly improved, especially in terms of charging time.

[0135] exist Figure 2 Another exemplary electrochemical storage device 100 is shown in FIG. The electrochemical storage device 100 includes an anode 110 having a silicon-carbon composite material 10. Figure 1 Compared to the embodiment shown in , the surface coating 11 of the silicon-carbon composite material 10 is partially applied to the surface area of ​​the silicon-carbon composite material 10 , so that a partial surface area of ​​the silicon-carbon composite material 10 remains without the surface coating 11 .

Claims

1. A silicon-carbon composite material (10), comprising: A porous carbon scaffold comprising micropores and mesopores and having a total pore volume greater than 0.5 cm 3 / g; - a silicon content in the range of ≥30 wt.-% to ≤75 wt.-%, relative to the silicon-carbon composite material (10); - nanoparticles comprising at least one of the elements Cu, Fe or Ni, wherein The nanoparticles are positioned on the surface of the silicon-containing carbon scaffold, and - nanowires, the nanowires being selected from silicon nanowires and carbon nanowires; wherein the nanowires are grown on the nanoparticles, and wherein a first surface coating is provided, the first surface coating being at least partially applied on a first surface region of the silicon-carbon composite material (10), the surface coating comprising at least one of the elements selected from C, Al, Si, Ti, Zr and Nb.

2. The silicon-carbon composite material (10) according to claim 1, wherein: The first surface coating is formed as a layer, wherein the layer of the first surface coating has a thickness of >0 nm to ≤0.3 nm and contains amorphous carbon or a metal oxide, the metal oxide being from at least one or more of the elements Al, Si, Ti, Zr and Nb or a combination of the above elements.

3. The silicon-carbon composite material (10) according to any one of claims 1 or 2, wherein: The first surface coating covers at least 50% of the surface area of ​​the silicon-carbon composite material (10).

4. The silicon-carbon composite material (10) according to any one of claims 1 to 3, wherein: The surface area of ​​the silicon-carbon composite material (10) is at least partially covered by the first surface coating and further at least partially covered by a second surface coating, wherein the second surface coating is at least partially applied on top of the first surface coating, at least partially applied next to the first surface coating, or at least partially applied on top of the first surface coating and next to the first surface coating.

5. The silicon-carbon composite material (10) according to claim 4, wherein: The second surface coating layer is formed as a carbon coating layer.

6. The silicon-carbon composite material (10) according to any one of claims 1 to 5, wherein: The nanoparticles include metal oxides of one or more elements from the group consisting of Cu, Fe, and Ni.

7. The silicon-carbon composite material (10) according to any one of claims 1 to 6, wherein: Silicon nanowires are provided, and the silicon nanowires include single crystal silicon and polycrystalline silicon, or a combination thereof.

8. A method for preparing a silicon-carbon composite material (10) according to any one of claims 1 to 7, wherein: The method comprises the following steps: -Providing porous carbon scaffolds with micropores and mesopores; - introducing into the micropores and mesopores of the porous carbon support a compound, in particular by chemical vapor infiltration, to form a silicon-carbon composite material, said compound comprising silicon and optionally also at least one of the elements Fe, Al, Ni, W and Ti, - attaching nanowires chosen from carbon nanowires and silicon nanowires to the porous carbon support, in particular by chemical vapor deposition, wherein the nanowires grow on nanoparticles located on the surface of the carbon support, wherein the nanoparticles comprise at least one element chosen from Cu, Fe and / or Ni; - At least a first surface coating is applied on a surface area of ​​the silicon-carbon composite material (10), the first surface coating comprising at least one element selected from the group consisting of C, Al, Si, Ti, Zr and Nb, and wherein the first surface coating at least partially covers the surface area of ​​the silicon-carbon composite material.

9. The method according to claim 8, wherein: At least one surface coating is applied via a vapor deposition method.

10. The method according to any one of claims 8 or 9, wherein: The first surface coating comprises a metal oxide from at least one of the elements Al, Si, Zr and Nb.

11. The method according to any one of claims 8 to 10, wherein: The silicon-carbon composite material (10) is treated with a metal alkoxide, a metal amide or an alkyl metal compound to form a treated compound surface, wherein the treated compound surface is treated with water or oxygen or ozone to form the first surface coating.

12. The method according to claim 11, wherein: The treatment of the silicon-carbon composite material (10) with a metal alkoxide or a metal amide or an alkyl metal compound to form a treated compound surface and the subsequent treatment of the treated compound surface with moisture or oxygen or ozone are repeated at least once.

13. The method according to any one of claims 11 or 12, wherein: During the treatment of the treated compound surface with moisture or oxygen or ozone, a temperature in the range of 150°C to 550°C is used.

14. An anode (110) for an electrochemical energy storage device (100), comprising the silicon-carbon composite material (10) according to any one of claims 1 to 7.

15. A method for manufacturing the anode (110) according to claim 14, wherein: The method comprises the following steps: - mixing the silicon-carbon composite material (10) according to any one of claims 1 to 7 with at least one carbon, - combining the mixture of the silicon-carbon composite material (10) and at least one carbon with at least one binder to form an electrode slurry, - applying the electrode slurry at least partially to at least one surface of an electrical conductor, such as a conductor foil, and - Drying the electrical conductor with the applied electrode slurry, in particular at a temperature of ≥ 100°C to ≤ 140°C, for forming the anode (110).

16. The method according to claim 15, wherein: The binder is used in an aqueous binder solution or in a non-aqueous binder solution, and wherein a paste-like electrode slurry is formed.

17. The method according to claim 15, wherein: A solid binder is used, and wherein a solid electrode slurry is formed.

18. The method according to claim 17, wherein: The solid electrode slurry is at least partially applied to at least one surface of an electrical conductor by a calendaring process.

19. An electrochemical storage device (100), in particular in the form of a lithium-ion battery, comprising: - at least one anode (110) according to claim 14; - at least one cathode (120); - a separator (130) disposed between the cathode (120) and the anode (110); and - An electrolyte (140) containing lithium ions.

20. An electric vehicle comprising an electric engine and an electrochemical energy storage device (100), wherein the electrochemical energy storage device is used to supply electric energy to the electric engine, characterized in that: The electrochemical energy storage device (100) is designed according to claim 19.

Citation Information

Patent Citations

  • Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof

    US20170170477A1